Laser Powder Bed Fusion of a Topology Optimized and Surface Textured Rudder Bulb with Lightweight and Drag-Reducing Design - Alessandro Scarpellini (Journal of Marine Science and Engineering, 2021)
This work demonstrates the advantages of using laser powder bed fusion for producing a rudder bulb of a moth class sailing racing boat via laser powder bed fusion (LPBF). The component was designed to reduce weight using an AlSi7Mg0.6 alloy and incorporated a biomimetic surface texture for drag reduction. For the topological optimization, the component was loaded structurally due to foil wing’s lift action as well as from the environment due to hydrodynamic resistance. The aim was to minimize core mass while preserving stiffness and the second to benefit from drag reduction capability in terms of passive surface behavior. The external surface texture is inspired by scales of the European sea bass. Both these features were embedded to the component and produced by LPBF in a single run, with the required resolution. Drag reduction was estimated in the order of 1% for free stream velocity of 2.5 m s−1. The production of the final part resulted in limited geometrical error with respect to scales 3D model, with the desired mechanical properties. A reduction in weight of approximately 58% with respect to original full solid model from 452 to 190 g was achieved thanks to core topology optimization. Sandblasting was adopted as finishing technique since it was able to improve surface quality while preserving fish scale geometries. The feasibility of producing the biomimetic surfaces and the weight reduction were validated with the produced full-sized component.